Evaluation of soil health under conventional and integrated organic farming systems models for upper Gangetic plain zone - KUMAR, AMIT; SHAMIM, M; PRUSTY, A K; KUMAR, LALIT; KUMAR, SUNIL; JAT, P C; SWARNAM, T P; MISHRA, R P; KASHYAP, POONAM; CHOUDHARY, JAIRAM; BHANU, CHANDRA; KUMAR, KAMLESH; et al. (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2021–2024 at ICAR-Indian Institute of Farming Systems Research, Modipuram, Meerut, Uttar Pradesh to evaluate the impact of Integrated Organic Farming System (IOFS) and Integrated Farming System (IFS) on soil biological properties namely microbial population, enzyme activities, and glomalin levels across cereal, vegetable, fruit and fodder crop systems. IOFS consistently demonstrated superior performance with respect to soil health indicators as compared to IFS. Higher microbial populations (bacteria, fungi, and actinomycetes) were observed under IOFS, particularly in vegetable crops. Soil under cereal crops (food system) showed around 41% increase in bacterial population in IOFS model compared to IFS model. Similarly soils under vegetable system showed 32% increase in fungal population in IOFS model. Enzyme activities, including dehydrogenase, β-glucosidase, urease, and alkaline phosphatase, were significantly higher in IOFS, with notable improvements in fruit and vegetable crops. Fodder system showed greater improvement in dehydrogenase (36.8%) and β-glucosidase (34.7%) under IOFS as compared to IFS. IOFS also showed increased levels of Easily Extractable Glomalin (EEG) and Total Glomalin (TG). Vegetable system showed 32% and 14% improvement in EEG and TG respectively, indicating enhanced arbuscular mycorrhizal fungi activity and potential for carbon and nitrogen sequestration. These findings highlight the benefits of organic nutrient and pest management practices in promoting soil fertility and sustainability.